Karst: Ditambang atau Dilestarikan, Konflik Sosial Rencana Pembangunan Pabrik Semen di Kabupaten Pati Jawa Tengah - Suharko, - (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2013)
The establishment of cement industry at regions with rich content of karst has increasingly grown in recent years. As a consequence, conflict of interest between cement company and local people groups has arised. The article aims to mapping out a natural resource based-conflict in district of Pati, province of Jawa Tengah. The social conflict has taken place at the stage of pra-construction of cement plant in the south Pati. The cement company, supported by local government, has continuously tried to establish the plant. The local people groups have always rejected it. Through organizing indigenous people, building social networks, and undertaking various collective actions, the local people groups have refused any efforts for establishing the plant. While this social conflict has continued, so far there is no an adequate conflict resolution. However, the new government of Central Java resulted from the 2013 election provides an opportunity to end the conflict.